REKONSTRUKSI VARIASI BULANAN SALINITAS DI JALUR ARUS LINTAS INDONESIA SELAMA ~ 200 TAHUN: REKAMAN SALINITAS DARI Î´18Ðž KARANG BUNAKEN DAN BALI - Indra Hernawan; Sri Yudawati Cahyarini; Mutiara Putri (Jurnal Geologi dan Sumberdaya Mineral, 2012)
Salinity is one of important parameter in oceanographic studies. The long timeseries oceanographic data is required to more understand the variability of oceanographic condition. Coral geochemical proxies overcome the shortcoming of instrumental data availibility. Î´18Ðž contents in coral skeleton is influenced by sea surface temperature and Î´18Ðž seawater. Î´18Ðž seawater is influenced by salinity. In this study salinity is reconstructed using coral Î´18Ðž and SST from the data model. Î´18Ðž from Bunaken and Padang Bai (Bali) corals are used in this study. SST data from the ERSST, SODA and HAMSON are used to reconstruct salinity. This study result in that the Bunaken coral records the local salinity variation in monthly and annual mean resolution. Padang Bai coral records better salinity in annual mean variation than in monthly variation. In both region, salinity variation in decadal resolution does not show significantly different.Keywords: Salinity, Sea surface temperature, Î´18Ðž, coral, Bunaken and Bali.